Can Prostate Specific Antigen Be Used as New Biomarker for Early Diagnosis of Breast Cancer? - Seyed Mostafa Shiryazdi; Mohammad Dehestani; Mohammad forat yazdi; Hamid Reza Soltani Gerdfaramarzi; Mansour Moghimi (Journal of Community Health Research, 2015)
Introduction: As a glycoprotein, Plasma Prostate-Specific Antigen (PSA) is mainly produced by prostate epithelial cells and is used as a major diagnostic tool for prostate cancer. A group of researchers relate the elevated number of estrogen receptors in breast cancer samples to the over-production of PSA in this type of cancer. Therefore, the present study aimed to determine the participants' plasma PSA level as a new biomarker for the primary diagnosis of breast cancer. Methods: Employing a historical cohort design, this study was conducted on 95 patients suffering from breast masses. The participants were assigned to malignant (n=43) and benign (n=40) groups. Male participants and those undergoing a recent hormone therapy were excluded from the study. Independent-samples t-test and Fishers exact test were applied to analyze the data using SPSS software (ver. 20). Results: The study findings indicated that the sensitivity and specificity of the plasma PSA level were respectively 63.15% and 53.48 % in patients suffering from the breast cancer. It was found that the mean plasma PSA levels for the benign and malignant groups were 0.047 ± 0.024 and 0.065 ± 0.054 respectively. No statistically significant relationship was detected between the two groups. Moreover, no significant difference was observed )P>0.05( between the two groups in regard with the background factors. Conclusion: Plasma PSA level is not a reliable biomarker to diagnose breast cancer, though regarding existing scientific evidence, more comprehensive studies are required to consider other features of malignant samples so as to evaluate the role of PSA in differentiating breast neoplastic lesions in a more meticulous way based on the degree of tumor differentiation.